The relationship between e‐learning and academic performance of students. Issue 3 (8th October 2020) - Rasheed, Hafiz Muhammad Wasif; He, Yuanqiong; Khalid, Junaid; Khizar, Hafiz Muhammad Usman; Sharif, Suhail
Abstract : The purpose of this paper is to investigate the relationship of service quality dimensions (tangibility, responsiveness, assurance, reliability, empathy, and e‐learning) on student's academic performance through student motivation, and student satisfaction. Primary data were collected from 384 participants studying in higher education institutes (HEI's) in the Punjab province of Pakistan and the research model was empirically tested. The findings reveal that all service quality dimensions (tangibility, responsiveness, assurance, reliability, empathy, and e‐learning) are positively associated with student's academic performance through student's motivation and student satisfaction. This study makes a substantial contribution to the literature of service quality, by adding a novel dimension "e‐learning" into the most renowned and frequently used SERVQUAL (tangibility, reliability, empathy, assurance, and responsiveness) model. By doing so we not only establish the link between e‐learning and student's academic performance through student satisfaction and student motivation but also extended the SERVQUAL model by incorporating an important neglected area.